Namelessness from Artaud to Beckett - Slote, Samuel (Brill, 2019)
Abstract After a period of electroshock therapy, Antonin Artaud claimed to have been able to regain his name and sense of self. The dehiscence of name and identification is reprised in Artaud’s final work, the radio play Pour en finir avec le jugement de Dieu. This consists of five texts, read by four people. Each text is followed by unintelligible, glossolalic screams performed by Artaud, as if Artaud were reacting against the speech acts performed by others in his name. The structure of this play suggests the predicament of Beckett’s Unnamable: an entity reacting in pain to its attempts to articulate itself in a language that is not his, but theirs. Résumé Après avoir subi une série d’électrochocs, Antonin Artaud déclara qu’il avait retrouvé son nom et son identité. La déhiscence du nom et de l’identité constitue un des sujets fondamentaux d’une des dernières œuvres d’Artaud: la pièce radiophonique Pour en finir avec le jugement de Dieu. Divisée en cinq textes, lus par quatre personnes et suivis de cris glossolaliques inintelligibles exécutés par Artaud, la pièce met en scène la réponse d’Artaud aux actes de parole effectués par autrui en son nom. La structure de cette pièce évoque l’Innommable de Beckett: un être qui tâche péniblement de s’articuler dans un langage qui n’est pas le sien.
Keywords: Samuel Beckett; Antonin Artaud; Gilles Deleuze; Irony; Nominalism; Jacques Derrida; Making Ireland; Antonin Artaud; Samuel Beckett